Analyzing 2-acetyl-4(5)-(1, 2, 3, 4-tetrahydroxybutyl)-imidazole in beverages by dispersive micro-solid phase extraction using polymer cation exchange sorbent followed by ion chromatography and liquid chromatography coupled with tandem mass spectrometry. (15th September 2019) - Wu, Chunjian; Wang, Li; Li, He; Yu, Shujuan
Highlights: The harmful substance THI in beverages was detected. Dispersive micro-solid phase extraction was performed for the extraction of THI. The identification and quantification of THI was by HPAEC-PAD and HPLC-MS/MS. Abstract: The presence of 2-acetyl-4(5)-(1, 2, 3, 4-tetrahydroxybutyl)-imidazole (THI) in beverages has raised several concerns regarding its toxicity to humans. The sample preparation and detection of THI in complex matrices is challenging owing to its high water solubility. Here we reported a rapid sample preparation method based on dispersive micro-solid phase extraction (D-μ-SPE) using polymer cation exchange sorbent as sorbent for the extraction of THI from beverage samples. THI was detected by high performance anion exchange chromatography-pulsed amperometric detector (HPAEC-PAD) and high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). The experimental parameters of D-μ-SPE on extraction efficiency were carefully optimized. Under the optimized conditions, high recoveries (83.4–96.1%) and good reproducibility (%RSD ≤ 8.7%) were obtained using D-μ-SPE-HPAEC-PAD and D-μ-SPE-HPLC-MS/MS. Limit of quantification was 75 ng/mL for HPAEC-PAD and 5 ng/mL for HPLC-MS/MS. This work proves the potential application the newly developed method for the quantification of THI in beverages containing caramel color.